NILAI-NILAI RELIGIUS DALAM NOVEL CINTA DALAM IKHLAS KARYA KANG ABAY DAN RENCANA IMPLEMENTASINYA - Fitri Atul Khotimah; Christanto Syam; Antonius Totok Priyadi (Universitas Tanjungpura, 2019)
AbstractThis research is motivated by literary works as an educational medium, so it must bring up various values. Research problems concerning the religious value of an individuals relationship with God, individual relationship with the individual itself, individuals relationship with others, individuals relationship with nature, and the implementation of literary learning in schools. The method used is descriptive method, in the form of qualitative, with a sociological approach to literature. Documentary data collection techniques, researchers data collection tools as instruments. Source of love novel data in sincere work by Kang Abay. Citation research data. The results of this study indicate that the individuals relathionship with God, the individual, the fellow human being, and nature include, prayer, laughter, meditation, fasting to God, maintaining self respect, gratitude, honesty, courtesy, patience, trust, right, demanding science, filial piety, loving family, upholding justice, spreading grace and love, to keep the promise, to protect the temple, to help, manage an conserve nature, to protect and preserve it. This research implementation plan is found in class XII at the high school lever or equivalent curriculum 2013 with basic competencies 3.3 analyzing novel texts and 4.3 producing coherent novel texts. Keywords: Analysis, religious values, love in sincerity